Pengaruh Terapi Progressive Muscle Relaxation dan Gerakan Sujud Terhadap Penurunan Tekanan Darah pada Pasien Hipertensi di Puskesmas Sukodadi Lamongan - Safitri, Dhea Afira; Faridah, Virgianti Nur; Lestari, Trijati Puspita (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Increased blood pressure remain major challenges for individuals with hypertension. Uncontrolled hypertension significantly raises the risk of cardiovascular complications such as stroke, kidney failure, and coronary heart disease, Thus, effective blood pressure management reduction strategies are essential to prevent severe complications. This study aims to determine the effect of Progressive Muscle Relaxation (PMR) therapy and sujud movements on lowering blood pressure in hypertensive patients at Sukodadi Community Health Center, Lamongan. A pre-experimental design with a one-group pre-post-test approach was used. The study sample consisted of 44 respondents selected through cluster random sampling. The intervention was carried out over two weeks, with four sessions, each lasting 20 minutes. Blood pressure measurements were conducted using a sphygmomanometer, The results of the Wilcoxon Signed Rank Test indicated a significant reduction in systolic (p = 0.000) and diastolic (p = 0.000) blood pressure. These findings demonstrate that the combination of PMR therapy and sujud movements was an effective non-pharmacological intervention for managing blood pressure in hypertensive patients. This approach has the potential to be routinely applied in primary healthcare settings as a holistic strategy for hypertension management.